Nasional Character-Based Education Quality Improvement Managemen in Early Childhood Education - Dwi Prasetiyawati Diyah Hariyanti; Fakhruddin Fakhruddin; Kardoyo Kardoyo; Mintarsih Arbarini (Universitas Negeri Semarang, 2023)
This study aims to describe the management of improving the quality of learning based on national character in early childhood education. So that these goals can be achieved properly, a qualitative approach is used with a literature study design in several PAUD institutions. Data was collected from school principals, teachers, educational staff and relevant references. The collected data were analyzed qualitatively descriptively. The results of the study show that: (1) planning for improving the quality of character-based learning is based on the national curriculum, school curriculum, school flagship programs and extracurricular activities with an integrated curriculum system; (2) the implementation of improving the quality of character-based learning is carried out based on a commitment to achieve the vision, mission and goals of the school with an active learning system, integrating character values ​​in the learning process, and intervention and habituation in instilling character values ​​in students; and (3) evaluation and quality control of character-based learning is carried out using an authentic assessment system.